PROBLEM APPROACH AND THE PRINCIPLE OF THE ROLE PERSPECTIVE IN THE PEDAGOGICAL PROCESS BASIS OF ACTIVATION PROFESSIONAL POSITION OF STUDENTS (Pedagogy of Higher and Secondary Education, 2003)
This article is devoted to forming o f active professional position future teachers by means o f using role perspective principle and problem approach during pedagogical training.